Serum and urine biochemical markers dynamics after using of laser therapy in patients with chronic posttraumatic osteomyelitis from endemic iodine deficiency regions - Shimon, Vasyl; Kubash, Volodymyr; Shimon, Mykhailo; Stoyka, Vasyl (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
The problem of diagnostic evaluation and treatment of patients with chronic post-traumatic osteomyelitis of long limb bones remains complex, multifaceted and not completely resolved in purulent orthopedics. Objective: to determine the biochemical markers of bone tissue in the blood and urine of patients with post-traumatic osteomyelitis for the primary assessment of their condition and control of the effectiveness of treatment. Methods: 47 patients were treated with post-traumatic osteomyelitis: 1st group (10 persons) received from non-endemic areas, 2nd (10) and 3rd (27) — f rom endemic (with iodine deficiency). In the 1st a nd 2 nd g roups t he s tandard t reatment s cheme w as used, in the 3rd it was supplemented with laser therapy. The controls used indicators of clinically healthy persons (20). Glycoproteins, alkaline and acidic phosphatase activity, sialic acids, chondroitin sulfates, total and ionized calcium were determined in the serum of blood; in the urine — the content of oxyproline and uronic acids. Results: Patients in group 1 have been gradually lowering biochemical markers of bone destruction and inflammation, starting from 7 days of treatment. Reduction in the level of excretion of oxyproline and uronic acids indicates a slowdown in catabolism of collagen and proteoglycans. In patients in group 2, the decrease in the content of glycoproteins, cholesterol and haptoglobin in serum was noted only 14 days after the start of treatment. Patients in the 3rd group recovered biochemical blood and urine output more intensively. Conclusions: post-traumatic osteomyelitis is characterized by an increase in serum of markers of inflammation and destruction of bone tissue, as well as catabolism of collagen and proteoglycans. The use of the treatment regimen using laser therapy had a higher clinical efficacy, which was confirmed by a decrease in the biochemical markers of inflammation and bone destruction during treatment.